A variety-specific arrangement of histone H1 subtype (H1.b and H1.z) polymorphic variants in differently plumaged quails. Issue 2 (4th March 2021) - Kowalski, A.; Knaga, S.
ABSTRACT: 1. This study was undertaken to evaluate genetic diversity among three varieties of Japanese quail (British Range, English White and Tuxedo) differing in plumage colour. The level of genetic variation was rated through the histone H1 polymorphic loci (H1.b and H1.z) containing quantitatively similar (P > 0.05) isoforms (H1.b1, H1.b2 and H1.z1, H1.z2) that form both homozygous (b1, b2 and z1, z2) and heterozygous (b1b2 and z1z2) phenotypes. 2. The complete set of histone H1 phenotypes were characteristic of the British Range and Tuxedo varieties. Phenotypes b2 and z2 were not detected in the English White variety. A lack of the former phenotypes resulted in excess of heterozygotes at loci H1.b (F = −0.563) and H1.z (F = −0.562), pointing to the presence of outbreeding. 3. The English White variety deviated from Hardy–Weinberg proportions (H1.b – Χ 2 = 7.61, P < 0.05 and H1.z – Χ 2 = 5.84, P < 0.05), in contrast to the British Range variety (H1.b – Χ 2 = 0.86, P > 0.05 and H1.z – Χ 2 = 0.86, P > 0.05) and Tuxedo (H1.b – Χ 2 = 1.6, P > 0.05 and H1.z – Χ 2 = 1.6, P > 0.05). The estimated values of the F ST index for loci H1.b (0.073) and H1.z (0.099) indicate a moderate genetic diversity of the quail population. 4. The distinct array and distribution of histone H1 phenotypes among quail varieties suggested that histone H1 allelic variants might have an individual impact on characteristic pigmentation of poultry.